A NEW IMPLEMENTATION TECHNIQUE FOR BUDDY SYSTEM - Abdullah, Nada; Younis, Manal (Iraqi Journal of Science, 2024)
Buddy system algorithm is dynamic memory control which is usually embedded inthe memory management unit, which is a part of the most widely use modern operatingsystems. Dynamic memory management is an important and essential part of computersystems design. Efficient memory allocation, garbage collection and compaction arebecoming increasingly more critical in parallel, distributed and real-time applicationsusing object-oriented languages like C++ and Java. In this paper we present a techniquethat uses a Binary tree for the list of available memory blocks and show how this methodcan manage memory more efficiently and facilitate easy implementation of well knowngarbage collection techniques.